Modeling and Optimal Control for Two-Wheeled Self-Balancing Robot - Do, Quoc-Thinh; Tran, Van-Thanh; Ngo, Minh-Thai; Tran, Minh-Quan; Thiem, Quan-Linh; Nguyen, Hoang-Son; Pham, Ba-Khoi; Phan, Nguyen-Phuoc-An; Nguyen, Duy-Hieu; Nguyen, Duc-Hoc; Nguyen, Van-Hoc; Tran, Ho-Minh-Quang; Le, ThiHongLam (Journal of Fuzzy Systems and Control, 2024)
The two-wheeled self-balancing robot based on an inverted pendulum model is a nonlinear object with uncertain parameters that are difficult to control with 6 state variables. This is a multiple input-multiple output (MIMO) under-actuated system that is very complex and causes many challenges for the operator. This paper analyzed the mathematical equation of a two-wheeled self-balancing robot vehicle system. Then, the Linear Quadratic Regulator (LQR) control is applied to the system through simulation on Matlab/Simulink and experiment. The results show that the LQR algorithm has been successfully applied in many moving cases.